The practice of Waqf land development in Malaysia: A social enterprise business perspective / Norinah Mohd Ali - Norinah , Mohd Ali (2020)
A large percentage (92.8 percent) of waqf lands in Malaysia are undeveloped due to inefficiency of waqf management and financing by the State Islamic Religious Councils (henceforth referred to as the Councils) that function as waqf trustees responsible for generating income from the current waqf to fulfill the needs of the beneficiaries and societies. In view of this issue, the objectives of this thesis are fourfold: (1) To examine the current waqf land development models employed by the Councils as social enterprises in Malaysia; (2) To examine the organizational strengths and weaknesses of the Councils in developing waqf lands; (3) To investigate perceived factors of the current waqf land development that contribute to the Councils’ success as social enterprises; and (4) To analyze the social impact of waqf land development to the communities. The study employs a mixed methods approach comprising both qualitative and quantitative. With regard to the qualitative method, semi-structured interviews were conducted with 22 waqf officers from 14 Councils across Malaysia. Meanwhile, for the quantitative approach, a survey questionnaire was employed to seek responses from 315 respondents from the communities who use and gain benefits from various categories of waqf land development. From interview data, themes were developed and organized into two categories; (i) the Councils’ practices for waqf land development and (ii) the social impact to the communities. Results from the interviews indicate that economic value is of primary importance when developing waqf lands for their sustainability. The interviews also reveal the income distribution model adopted by the Councils for waqf land development. There are nine factors for current waqf land development that contribute to the Councils’ success as social enterprises: (1) various types of waqf development; (2) sustainability; (3) opportunity; (4) knowledgeable; (5) financing creativity; (6) monitoring; (7) support; (8) public involvement; and (9) human development. Meanwhile, results from the questionnaire survey manifest that waqf benefits emerged from various categories of waqf land development are the most needed by the communities. The results further indicate that there is a significant difference between the needs of the communities and their satisfaction towards waqf land development. Further, the results evince, all mean scores for the needs of communities are higher than the mean score for their satisfaction. As such, the results provide empirical evidence that the current waqf land development has not met the needs of the communities. This study contributes to the literature on social enterprise business model for waqf activity, and waqf communities. Furthermore, it provides a methodological contribution through the formulation of questionnaire concerning waqf land development based on findings from qualitative data. The main implication of this study is that, it provides new and relevant perspectives on future waqf land development beneficial to the Councils and other waqf institutions.